(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Natural polyphenols are well-known to have the chemical and physical qualities that helpprotect vital biomolecules including lipids, proteins, and nucleic acids against oxidation. Specificenzymatic measurements and non-specific indicators were used to assess the level of oxidative stress inexperimentally produced arterial hypertension by the administration of L-NAME. Results demonstratedthe antioxidant and protective effect of Sambucus nigra extract on biochemical markers and histologicalchanges in experimental arterial hypertension. Glutathione-peroxidase and superoxide-dismutaseactivities are markedly reduced in the hypertension group compared to the polyphenol-protected group.The polyphenolic extract of Sambucus nigra may be useful as a nutritional supplement in chroniccardiovascular and metabolic illnesses if its effects on the functionality of endothelial cells, such asmembrane sensitivity and intracellular signalling, are understood.